Pengaruh Return On Asset (ROA), Current Ratio (CR) Dan Debt To Equity Ratio (DER) Terhadap Return Saham Yang Terdaftar Pada Indeks LQ45 Di BEI Tahun 2019-2021 - Lathifah Nurul Hidayah; Shadrina Hazmi (AKUNTANSI 45, 2023)
The purpose of this study was to determine the effect return on asse, current ratio and debt to equity ratio on stock returns. The population in this study are all companies except mining and banking sector companies listed on the LQ45 index on the Indonesia Stock Exchange (IDX) for the 2019 – 2021. The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 24 companies and total sample of 72. The method of analysis in this study used multiple linier regression analysis supported by the SPSS 21 application. The result of this study indicate that Return On Asset does not have a significant effect on stock returns, Current Ratio has a positive and significant effect on stock returns, Debt to Equity Ratio has no effevt on stock returns and Return On Asset, Current Ratio and Debt to Equity Ratio together affect stock returns.